2010
DOI: 10.1007/s10682-010-9386-1
|View full text |Cite
|
Sign up to set email alerts
|

Fight or flight: plastic behavior under self-generated heterogeneity

Abstract: Plants are able to plastically respond to their ubiquitously heterogeneous environments; however, little is known about the conditions under which plants are expected to avoid or confront their neighbors in dense stands, where heterogeneity is selfgenerated by non-uniform growth and feedback between plant interactions and stand heterogeneity. We studied the role of plasticity for spatial pattern-formation and the resulting stand-level fitness of clonal plants, assuming variable types of plastic behavior. Speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 69 publications
0
18
0
Order By: Relevance
“…Numerous studies demonstrated that trait plastic responses (Bittebiere, Renaud, Clément, & Mony, 2012;Herben & Novoplansky, 2010;Turkington, Hamilton, & Gliddon, 1991), related to processes of stabilising niche differences or increasing competitive ability (Chesson, 2000;Turcotte & Levine, 2016), depend on competitor identity. In particular for intraspecific competition, a niche differentiation process should limit the competition intensity through horizontal traits plasticity, allowing complementary ramet positioning (Herben, Krahulec, Hadincová, & Pecháčková, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies demonstrated that trait plastic responses (Bittebiere, Renaud, Clément, & Mony, 2012;Herben & Novoplansky, 2010;Turkington, Hamilton, & Gliddon, 1991), related to processes of stabilising niche differences or increasing competitive ability (Chesson, 2000;Turcotte & Levine, 2016), depend on competitor identity. In particular for intraspecific competition, a niche differentiation process should limit the competition intensity through horizontal traits plasticity, allowing complementary ramet positioning (Herben, Krahulec, Hadincová, & Pecháčková, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…However, research on clonal plant growth has demonstrated that clonal growth is often plastic in response to environment (Novoplansky et al 1990;Hutchings and De Kroon 1994;Skálová et al 1997) and this plasticity can be ecologically relevant (Berg and Ellers 2010;Herben and Novoplansky 2010). Using this line of argumentation, Sammul (2011) examined whether spacer length, or its intraspecific variation, are good explanatory variables for plant distribution in Estonian wooded meadows (subjected to different management regimes and differing in their resource heterogeneity levels).…”
Section: Key Findingsmentioning
confidence: 99%
“…Thus, it is logical to ask: what rooting strategies lead to the greatest competitive ability and highest returns on fitness? Cahill and McNickle 2011; Herben and Novoplansky 2010; Litav and Harper 1967; Parrish and Bazzaz 1976; Schenk et al 1999; Litav and Harper 1967; Craine et al 2005; Gersani et al 2001, Campbell and Grime 1989; Parrish and Bazzaz 1976; Parrish and Bazzaz 1976; Schenk et al 1999; Hess and de Kroon 2007; Litav and Harper 1967; McNickle et al 2008; Mommer et al 2011; Schenk et al 1999.…”
Section: Introductionmentioning
confidence: 99%
“…A second group of plant ecologists are skeptical of these game theoretic models of root production (de Kroon et al 2012; Herben and Novoplansky 2010; Hess and de Kroon 2007; Laird and Aarssen 2005; Schenk 2006; Semchenko et al 2007). This skepticism seems to be well founded, and there is evidence that many plants do not engage in these plastic pre-emptive games (Cahill et al 2010; Semchenko et al 2007; Semchenko et al 2010).…”
Section: Introductionmentioning
confidence: 99%